The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1741-3729.2000.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

When Mothers Turn to Their Adolescent Daughters: Predicting Daughters' Vulnerability to Negative Adjustment Outcomes*

Abstract: Mother-to-daughter disclosure regarding two sensitive topic areas-financial concerns and complaints/anger toward the ex-husband (the adolescent girl's father)-was examined in a sample of 62 mother/adolescent-daughter dyads following the mother's divorce. Most mothers in the current sample have disclosed to their daughters on these two topics, but with varying levels of detail and diverse motivations. Daughter perceptions of maternal disclosure were associated with daughter psychological distress, regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 52 publications
(58 reference statements)
3
35
1
1
Order By: Relevance
“…However, in 16 cases the adolescent was ineligible for participation either because he or she was 18 or older or because it was clear that one person had completed both the mother and the adolescent questionnaire, making the data unusable. The final response rate was 35%, which compares favorably to rates in previous research efforts using court records (see Cantrell and Sprenkle 1989;Koerner et al 2000).…”
Section: Participants and Proceduresmentioning
confidence: 61%
See 4 more Smart Citations
“…However, in 16 cases the adolescent was ineligible for participation either because he or she was 18 or older or because it was clear that one person had completed both the mother and the adolescent questionnaire, making the data unusable. The final response rate was 35%, which compares favorably to rates in previous research efforts using court records (see Cantrell and Sprenkle 1989;Koerner et al 2000).…”
Section: Participants and Proceduresmentioning
confidence: 61%
“…Previous research has also found that negative maternal disclosure about the former husband/adolescent's father is troublesome to adolescents (Hetherington 1999) and is associated with adolescents' psychological distress-symptoms of depression and anxiety (Koerner et al 2000;Koerner et al 2004;Koerner et al 2002). Surprisingly, however, researchers have not yet examined the possible negative consequences of such disclosure on adolescents' perceptions of the quality of the father-adolescent relationship.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations